Copreneurs: The Impact of Spousal Relationships on Business success In Nigeria - Aladejebi, Olufemi (Archives of Business Research, 2020)
Copreneurship is a term used to describe a situation where the husband and wife manage the same company. Copreneurship is a branch of the family business. It is becoming popular among the type of businesses. The main objectives of this research study include the examination of how spousal relationships affect a firm's financial profitability, factors that limit and improve the effective functioning of copreneurial teams, and how decisions are made. A purposeful sample was used to select respondents. Data was collected from fifty-five (55) couples out of which forty- seven (47) were viable. The research instrument was based on a five-point Likert scale. The questionnaire administered contained 2parts, Part 1: contains general information while Part 2: contains Perceived success, financial performance, growth performance, shared dream, Leadership, personal needs alignment, Division of labour, complementary skills, supportive employees, competencies, adequate resources. The results showed that the primary operators of the businesses were mostly wives. The majority of the copreneurs benefitted greatly from their business relationship in terms of perceived success, financial performance, growth performance, and shared dreams.